Type, areal extent and localization of carcass contaminations during industrial pig slaughter - Tholen, Janna; Grosse-Kleimann, J.; Schulze Althoff, G.; Kreienbrock, L.; Upmann, Matthias (Meat Science)
The aim of the study is to provide an up-to date overall evaluation of visual contamination occurring on the slaughter line in order to provide a basis for implementing contamination control measures and to the hygienic quality of the processes. For this purpose, 627 contaminated pig carcasses in an industrial slaughterhouse in north western Germany were examined in 2021 for its distribution of type, areal extent and localization of slaughter contamination. Prior to official meat inspection, two persons visually scanned dorsal and ventral surfaces of the eviscerated but not yet split pig carcasses from cranial to caudal and recorded types, areal extent and localization of the contamination. The main contamination type were intestinal contents, bile, stomach contents, tubular rail fat and “others”, which mostly consisted of a reddish foam from the respiratory tract. 103 out of 627 contaminated animals showed more than one contamination, which leads to a total number of 754 contaminations detected. Intestinal contents accounted for almost half of all contaminations and “others” for 30%. Forelimb, back and ham together counted for 70% of the contaminated regions. The affected area was smaller than that of a one euro coin (diameter about 23 mm) in 86% of the cases.
Keywords: Abattoir; Slaughter hygiene; Evisceration; Pork production; Pig carcass contamination; Fecal contamination; Bile contamination; Meat inspection